Safety and efficacy of ADS-5102 (amantadine) extended release capsules to improve walking in multiple sclerosis: A randomized, placebo-controlled, phase 2 trial. (April 2019) - Cohen, Jeffrey A; Hunter, Samuel F; Brown, Theodore R; Gudesblatt, Mark; Thrower, Ben W; Llorens, Lily; Souza-Prien, Cindy J; Ruby, April E; Chernoff, David N; Patni, Rajiv
Background: Walking impairment causes disability and reduced quality of life in patients with multiple sclerosis (MS). Objective: Characterize the safety and efficacy of ADS-5102 (amantadine) extended release capsules, 274 mg administered once daily at bedtime in patients with MS with walking impairment. Methods: This randomized, double-blind, placebo-controlled, 4-week study was conducted at 14 trial sites in the United States. Study objectives included safety and tolerability of ADS-5102, and efficacy assessments (Timed 25-Foot Walk (T25FW), Timed Up and Go (TUG), 2-Minute Walk Test, and Multiple Sclerosis Walking Scale-12). Fatigue, depression, and cognition also were assessed. Results: A total of 60 patients were randomized (30 to ADS-5102 and 30 to placebo); 59 of whom were treated. The most frequent adverse events (AEs) were dry mouth, constipation, and insomnia. Five ADS-5102 patients and no placebo patients discontinued treatment due to AEs. One patient in the ADS-5102 group experienced a serious AE—suspected serotonin syndrome. A 16.6% placebo-adjusted improvement was seen in the T25FW test ( p  < 0.05). A 10% placebo-adjusted improvement in TUG was also observed. No changes in fatigue, depression, or cognition were observed. Conclusion: ADS-5102 was generally well tolerated. These data demonstrate an effect of ADS-5102 on walking speed. Further studies are warranted to confirm these observations.